CRITERIA OF RATIONAL PHARMACOTHERAPY AS SHOW-CASED BY THE SELECTION OF VITAMIN-MINERAL COMPLEX IN PEDIATRICS - S.V. Talashova (Union of pediatricians of Russia, 2010)
Currently the issue of the right selection and justified use of medications is an especially critical one. A variety of medications in many aspects causes the major issue of incorrect prescription of drugs. The article gives criteria for the rational pharmacotherapy as showcased by vitamin-mineral complexes and makes specific recommendations on the use of that group of preparations.Key words: vitamin-mineral complexes, rational pharmacotherapy, pediatrics. (Pediatric Pharmacology. - 2010; 7(1):81-84)